1976
DOI: 10.1002/cne.901700304
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the naturally occurring motor neuron loss by enlargement of the periphery

Abstract: Motor hyperplasia following the enlargement of the periphery by implantation of a supernumerary leg is not due to "remote control" of proliferation, as shown by motor neuron counts in 6-day chick embryos. We have tested the alternative hypothesis that we are dealing with reduction of the naturally occurring cell death. In normal development, the lumbar lateral motor column (l.m.c.) undergoes motor neuron degeneration resulting in a cell loss of at least 40%, which occurs between six and one-half and nine and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
131
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(139 citation statements)
references
References 16 publications
7
131
1
Order By: Relevance
“…Similar findings are seen when the target size is reduced by genetic manipulation or somite removal (Phelan and Hollyday, 1991;Grieshammer et al, 1998;Kablar and Rudnicki, 1999). These findings are complimented by studies that show that the addition of a supernumerary limb increases the number of surviving MNs on the ipsilateral side (Hollyday and Hamburger, 1976).…”
Section: Introductionsupporting
confidence: 59%
“…Similar findings are seen when the target size is reduced by genetic manipulation or somite removal (Phelan and Hollyday, 1991;Grieshammer et al, 1998;Kablar and Rudnicki, 1999). These findings are complimented by studies that show that the addition of a supernumerary limb increases the number of surviving MNs on the ipsilateral side (Hollyday and Hamburger, 1976).…”
Section: Introductionsupporting
confidence: 59%
“…In chick embryos, it was demonstrated that the removal of leg or wing buds during early developmental stages resulted in a virtually complete loss of the corresponding motoneurons analyzed at later developmental stages (31). Conversely, the implantation of an additional extremity anlage resulted in an increase of the number of motoneurons projecting into the augmented target area (31,37). The further extension and evaluation of this concept, replacing the physiological target of motoneurons by sarcoma tissue, resulted-by a cascade of lucky coincidences-in the discovery of nerve growth factor (NGF) (summarized in 48), the molecular incarnation of the retrograde trophic influence of peripheral target cells on sympathetic and subpopulations of sensory (both neural crest and placode derived) neurons (summarized in 4,48,104).…”
Section: Introductionmentioning
confidence: 99%
“…For example, nerve growth factor (NGF) is known to be produced in limiting amounts in the target tissues of peripheral sympathetic and sensory neurons, and considerable evidence has been accumulated demonstrating that NGF supports the survival of these cells during critical stages of development (for review, see Barde, 1989). Similarly, motoneurons have been shown to rely upon their target during the embryonic period of naturally occurring cell death (Hamburger, 1958;Hollyday and Hamburger, 1976). In addition, a number of groups have described the ability of extracts of skeletal muscle, the target of motoneurons, to promote the survival of motoneurons in culture (Bennett et al, 1980;Schnaar and Schaffner, 1981;Calof and Reichardt, 1984;Kaufman et al, 1985;Flanigan et al, 1985;Smith et al, 1985;Dohrmann et al, 1986;O'Brien and Fischbach, 1986;Martinou et al, 1989;Arakawa et al, 1990;Bloch-Gallego et al, 1991;Jeong et al, 1991).…”
Section: Introductionmentioning
confidence: 99%